The Language Ambiguity in English Literature a 2024 Class at State University of Medan - Juan Barus; Meliana Napitu; Dinda Sabrina; Valendeo Pangaribuan; Muhammad Natsir (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The topic of this research is language ambiguity that is often spoken by every student in English Literature A class of 2024 at Medan State University. This research aims to answer